Strategic Framework Deployment for Elevating Educational Governance Standards - Ghafar, Muhammad; Shiddiq, Jamaludin; Yang, Li; Hamidah, Noor Zinatul (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
Strategic planning has been applied to social organizations, including in education. This study aimed to find and examine the process of preparing and implementing strategic plans and their impact on governance quality at Madrasah Aliyah Amanatullah. This research is field research with a qualitative approach—information obtained through observation, interviews with primary data sources, and documentation. Data were analyzed by data reduction, presentation, and inference using domain analysis. The validity of the data uses intensive observation and triangulation criteria. The study findings indicate that the process of developing a strategic plan involves several steps. Firstly, it involves formulating the school's vision, mission, and goals with the participation of all stakeholders. Next, a strategic planning team is formed. The process then includes analyzing strategic planning and evaluating strategic options. Secondly, the implementation process is executed by assigning tasks and collaborating to implement strategic planning, as well as evaluating its execution. Thirdly, the effect of enhancing school governance includes the implementation of guidelines to improve the quality of educators and education staff, the enhancement of service governance to students, and the establishment of practical cooperation with all stakeholders of Madrasah Aliyah Amanatullah.